Ecological speciation associated with elevation in a tropical passerine bird: a morphological, genetic, and behavioral approach (2010)
The study of elevational gradients is of importance in evolutionary biology because it can give us insights related to local adaptation and speciation associated with elevation. Multiple studies have revealed local adaptation along elevational gradients leading to eventual divergence between populations. However, little is known about the origin of this divergence and the processes that keep the species separate. We present the most complete analysis related to the differentiation of a montane bird population along an elevational gradient, focusing on the Gray-brested Wood-wren (Henicorhina leucophrys:Troglodytidae). Using morphological, genetic and behavioral data, we observed divergence in phenotypic and vocal traits consistent with different adaptive scenarios and evidence for reproductive isolation between the two forms that occur along the elevational gradient. Additionally, phylogenetic analyses revealed that the pattern of elevational replacement is the result of secondary contact following an allopatric phase and not product of parapatric ecological speciation. These results provide important empirical evidence consistent with the acoustic and morphological adaptation hypothesis and the process of speciation along elevational gradients in montane birds.